Clinical and radiological evaluation of ejaculatory duct obstruction - Onur, Mehmet Ruhi; Orhan, Yrfan; Fyrdollap, Fatih; Onur, Rahmi; Kocakoc, Ercan (Taylor & Francis Inc, 2007)
Ejaculatory duct obstruction (EDO) is a rare but surgically correctable cause of male infertility. With the advent and increased use of transrectal ultrasonography and magnetic resonance imaging, abnormalities of the ejaculatory duct (ED) related to infertility have been diagnosed more frequently. Recently, with the increased awareness of functional obstruction of ED, reports have been focusing on the diagnosis of partial or functional EDO. We present 2 review of the ED pathologies, imaging modalities and treatment options.
Keywords: ejaculatory duct obstruction; infertility; magnetic resonance imaging; ultrasonography